Faktor Penyebab Meningkatnya Pe’laku Judi Online pada Pelajar di Masa Pandemi Covid-19 (Studi Kasus di Kelurahan Mangga) - Zekel Calvin Ginting; Bengkel Ginting (Yayasan Literasi Sains Indonesia, 2023)
From Google data or digital search, Medan City itself was counted before the occurrence of COVID-19; from 2010 until the start of the emergence of COVID-19, it was recorded that only 28% accessed online gambling through web searches on Google. Meanwhile, after COVID-19 until now, there has been an increase of 29%, from the previous 28% to 57%. Of course, this is a very significant increase between before and after COVID-19. The purpose of this study was to find out the factors causing the increase in online gambling among students during the COVID-19 pandemic in the Mangga Village. Data collection was carried out using data triangulation techniques, namely by combining three data collection techniques (observation, interview, and documentation). The results of research and observation of research subjects found that the factors causing the increase in online gambling among students during the COVID-19 pandemic in the Mangga Village were divided into internal and external factors. Internal factors that are the cause of the increase in online gambling players are due to the inability of students to absorb the values and norms that apply, and there is also an outlet for feelings of disappointment from these students. As for external factors, namely the existence of economic problems, the influence of the community environment, and the influence of technological progress,